Diagnostic Value of Magnetic Resonance Imaging in Fibrodysplasia Ossificans Progressiva. (28th April 2020) - Botman, Esmée; Teunissen, Bernd P; Raijmakers, Pieter; de Graaf, Pim; Yaqub, Maqsood; Treurniet, Sanne; Schoenmaker, Ton; Bravenboer, Nathalie; Micha, Dimitra; Pals, Gerard; Bökenkamp, Arend; Netelenbos, J Coen; et al.
ABSTRACT: Using [ 18 F] Sodium Fuoride (NaF) Positron Emission Tomography (PET) it is not only possible to identify the ossifying potency of a flare‐up, but also to identify an asymptomatic chronic stage of fibrodysplasia ossificans progressiva (FOP). The purpose of this study was to investigate the diagnostic role of a more widely available imaging modality, Magnetic Resonance Imaging (MRI), which is of special interest for studies in pediatric FOP patients. MRI and [ 18 F]NaF PET/CT images at time of inclusion and subsequent follow‐up CT scans of 4 patients were analyzed retrospectively. Presence, location, and intensity of edema identified by MRI were compared with activity on [ 18 F]NaF PET. Occurrence or progression of heterotopic ossification (HO) was examined on the follow‐up CT images. Thirteen different lesions in various muscle groups were identified: five lesions with only edema, five lesions with both edema and increased [ 18 F]NaF uptake, one lesion with only increased [ 18 F]NaF uptake, and two lesions with neither edema nor uptake of [ 18 F]NaF. Mild edema, found in three lesions, was present at asymptomatic sites, which did not show increased [ 18 F] NaF uptake or progression of HO on consecutive CT images. Moderate edema was found in three symptomatic lesions, with increased [ 18 F]NaF on PET and progression of HO on CT. Severe edema was identified in four lesions. Interestingly, two of these lesions did not develop HO during follow‐up; one of these two even gave obvious symptoms of a flare‐up. MRI can identify whether symptoms are the result of an acute flare‐up by the presence of moderate to severe edema. The occurrence of severe edema on MRI was not always related to an ossifying lesion. The additional diagnostic value of MRI requires further investigation, but MRI does not seem to fully replace the diagnostic characteristics of [ 18 F]NaF PET/CT in FOP. © 2020 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.